A survey of vertical handover decision algorithms in fourth generation heterogeneous wireless networks - Mahmood, Adnan; Hushairi, Zen; Al-Khalid, Othman (International Digital Organization for Scientific Information, 2013)
Vertical handover decision (VHD) algorithms are indispensable components of the forthcoming Fourth Generation (4G) heterogeneous wireless networks architecture - so as to provide the requisite Quality of Service (QoS) to an assortment of applications anywhere at anytime, while allowing seamless roaming in highly dynamic scenarios (i.e. multitude of access network technologies) using terminals enabled with multiple access interfaces. This paper intends to present a comprehensive overview/survey of the VHD algorithms designed to satisfy these requirements, along with the main algorithms, protocols and tools proposed in the literature. To offer a systematic comparison, our survey categorized the algorithms in four groups based on the main handover decision criteria used. The survey revealed the need for devising an efficient algorithm which is truly useful in a wide ranging conditions, network parameters and user preferences